Методичний підхід до вибору системи оподаткування підприємств малого бізнесу - Рета, Марина; Погорєлов, Ігор Миколайович; Лущицька, Марія (Тернопільський національний технічний університет ім. Івана Пулюя, 2013)
Протягом тривалого періоду на рівні законодавства розробляються та впроваджуються альтернативні системи оподаткування, які дають можливість підприємствам малого бізнесу не тільки спростити облікові процедури, але й зменшити податкове навантаження. Вибір системи оподаткування має бути зваженим та методично обґрунтованим. У зв’язку з цим у статі розглянуто підхід щодо прийняття рішення про вибір системи оподаткування малим підприємством на основі відносного критерію – рентабельності продажу. Використання такого підходу дозволяє платникові прийняти рішення відносно переходу на певну альтернативну систему оподаткування або про недоцільність такого переходу. Наведено числові приклади, які наочно підтверджують доцільність та простоту використання запропонованого підходу.

For national economy small business is one of the main factors of development. After all economic development of the country is inseparably linked with growth of enterprise activity. The taxation of subjects of small business represents one of the most important and most effective levers of state regulation of market economy. In article legislative approaches to criteria of definition of subjects of small business are analysed, divergences in legislative documents are revealed. Conditions and practical opportunities of transition of small enterprise on alternative system of the taxation are analysed. During the long period at the level of the legislation alternative systems of the taxation which give the chance to small business enterprises are developed and take root not only to simplify registration procedures, but also to reduce tax loading. The choice of system of the taxation has to be weighed and methodically reasonable. In this regard in article approach to making decision on a choice of system of the taxation small enterprise on the basis of relative criterion - profitability of sales is considered. Use of such approach allows the payer to make the decision concerning transition to a certain alternative system of the taxation or on inexpediency of such transition. In article numericalexamples which visually confirm expediency and simplicity of use of the offered approach are given. Features of offered approach consist that problems of use of alternative systems of the taxation are investigated not only from positions of state regulation of economy, but, first of all, from the point of view of opportunity and expediency of use by subjects of small business. Besides, the offered approach doesn't exclude use of other criteria of decision-making, and on the contrary, supplements them and expands opportunities from the point of view of suspension and validity.
Methodical approach to the choice of system of the taxation of small business enterprises
Keywords: підприємство мале; податок; рентабельність продажу; ефект економічний; прибуток чистий; small business; tax; return on sales; economic impact; net income